The importance of mutual beneficial relationships in the sponsorhip dyad - Gerd Nufer; André Bühler (Hochschule Reutlingen, ESB Business School, 2010)
The emphasis on relationships - as opposed to transaction-based exchanges - is redefining the marketing domain. Sports sponsorship is an important source of income for professional sporting organisations and an effective marketing tool for companies aiming at commercial objectives through sports sponsorship. The most successful sports sponsorships are based on a good relationship between the sports entity and its sponsor. The paper describes the nature of relationships between a professional sporting organisation and its most important primary and secondary customers with special emphasis on sponsors. Based on recent studies the main factors for successful relationships in the context of sports sponsorship are identified and discussed.
urn:nbn:de:bsz:21-opus-45840
Keywords: 650